THE DEVELOPMENT OF BIOLOGY MATERIAL RESOURCES BY METACOGNITIVE STRATEGY - Endang Susantini (Universitas Negeri Malang, 2016)
The Development of Biology Material Resources by Metacognitive Strategy The study was aimed at finding out the suitability of Biology Materials using the metacognitive strategy. The materials were textbooks, self-understanding Evaluation Sheet and the key, lesson plan, and tests including the answer key. The criteria of appropriateness included the relevance of the resources with the content validity, face validity and the language. This research and development study was carried out employing a 3D model, namely define, design and develop. At the define stage, three topics were selected for analysis, they were virus, Endocrine System, and Genetic material. During the design phase, the physical appearance of the materials was suited with the Metacognitive Strategy. At the develop phase, the material resources were examined and validated by two Biology experts and senior teachers of Biology. The results showed that the Biology material Resources using Metacognitive Strategy developed in the study has fell into the category of very good ( score > 3.31) and was therefore considered suitable.